Pengamanan Data Teks Dengan Menggunakan Algoritma Zero-Knowledge Proof - Toyib, Rozali; Darnita, Yulia (UNIVED Press, 2020)
Data security is very important in maintaining the confidentiality of the information itself, especially if the information is only known to certain parties. Sending data or information without security will be at risk of eavesdropping. So that the information contained in it can easily be known by unauthorized parties, and something like that is very detrimental. Until now, cryptography is one solution to guarantee the security of information. Zero Knowledge Proof (ZKP) is a cryptographic protocol that can be used by someone to prove one's ownership (prover) of confidential information to another person (verifier), without the need to reveal the information or provide a way for other people to know the secret. The test result is that Zero Knowledge Proof divides a data stream into small blocks. Each of these blocks is encrypted separately. In a zero knowledge proof implementation, the key to encrypt will only be with the user, and with that, he will be able to encrypt and decrypt information. The zero knowledge proof algorithm is a unique method by which a user can prove to other users that he knows additional information.